Implementation of Problem-Based Learning Model based on Differentiated Learning to Improve Science Literacy Skills and Student Activities - Virlya Citra Dewi; Nur Kuswanti; Bambang Prijono (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2023)
Scientific literacy skills are a person's ability to understand and construct scientific concepts so that they can apply them scientifically to respond to environmental issues and solve their problems. This skill is essential to train students so that students are more involved and active in learning. The low level of scientific literacy skills and student activity is a problem that is often faced by Indonesian teachers. This study aims to improve scientific literacy skills and student activity through problem-based learning based on a differentiated learning approach. This type of research is Classroom Action Research (CAR), which consists of four stages: planning, action, observation, and reflection. Data collection techniques in this study are observation and tests. The research instrument was an observation sheet to determine student learning activities, while a test sheet was used to determine students' literacy skills. Based on the study's results, it showed an increase in scientific literacy skills and student activity in each cycle. This can be seen from the N-gain value of the first cycle (0.63) and the second cycle (0.71), and the average of student activity in the first cycle (70.32%) and the second cycle (88.44%). Thus, it can be concluded that the implementation of problem-based learning based on a differentiated learning approach can improve scientific literacy skills and student activity.